EFEKTIVITAS KONSELING KELOMPOK TEKNIK COGNITIVE RETRUCTURING UNTUK MEREDUKSI PERBANDINGAN SOSIAL MALADAPTIF PADA MURID - Septiani Nur Azizah; Agus Afriliyanto; Yanuari Srianturi (IKIP Siliwangi, 2026)
The high use of social media, especially the TikTok platform among students, has led to a tendency for maladaptive socialcomparison, so appropriate interventions are needed in counseling guidance services. This study uses the Cognitive BehavioralTherapy (CBT) approach with Cognitive Restructuring techniques in group counseling services. The aim of this study was toevaluate how well cognitive method-based group counseling interventions can reduce these tendencies. This study used a quasi-experimental method with a non-equivalent control group design and sampling using purposive sampling techniques. The datacollection technique uses a maladaptive social comparison scale through pre-test and post-test. The average pre-test scores of the control and experimental groups were 103.83 and 104.00, respectively. The post-test results showed that the average score of theexperimental group dropped to 67.33, while the control group was 120.17. H0 was rejected because the results of the paired samplet-test of the experimental group showed a significance score of less than 0.001 (p < 0.05). These findings show that the interventionsgiven are effective in reducing maladaptive in students.